2016
DOI: 10.1049/iet-nbt.2016.0028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ball milling on the particle size and antimicrobial properties of Tridax procumbens leaf nanoparticles

Abstract: The herbal nanoparticles were prepared from shade dried plant leaves employing ball milling technique using different process parameters, like ball ratio/size and milling time. The obtained nanoparticles were comprehensively characterised using X-ray diffraction, Fourier transform infrared spectroscopy, UV-visible spectroscopy, dynamic light scattering, scanning electron microscopy and antimicrobial analysis techniques. The crystallinity of the nanoparticles was retained without altering even though the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…The coarse powder was milled for 1 h using 20 mm sized balls (Zirconia) using Ball mill (PM100; Retsch, Germany) at 300 rpm to get fine powder. The obtained fine powder was again milled (10 mm balls: 300 rpm, 20:1 ball ratio) for 15 h. The powder was collected for further characterisation studies, followed by coating on fabrics as per the protocol reported in our earlier investigations [27, 28].…”
Section: Methodsmentioning
confidence: 99%
“…The coarse powder was milled for 1 h using 20 mm sized balls (Zirconia) using Ball mill (PM100; Retsch, Germany) at 300 rpm to get fine powder. The obtained fine powder was again milled (10 mm balls: 300 rpm, 20:1 ball ratio) for 15 h. The powder was collected for further characterisation studies, followed by coating on fabrics as per the protocol reported in our earlier investigations [27, 28].…”
Section: Methodsmentioning
confidence: 99%
“…The XRD pattern of AINPs is shown in Fig. 2, which conrms the absence of diffraction peaks i.e., amorphous nature, except for the observed broad band at 2q values (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Generally, the amorphous nature of the particles is non-toxic to living organisms and hence, amorphous herbal nanoparticles enhance the biocompatibility for clinical applications.…”
Section: Characterizationmentioning
confidence: 99%
“…Aer milling, the nanoparticles were taken for biological studies, followed by different characterization studies as reported in our previous investigations. [27][28][29] The protocol for the preparation of herbal nanoparticles from A. indica leaves is shown in Fig. 1.…”
Section: Collection Of Samples and Preparation Of Herbal Nanoparticlesmentioning
confidence: 99%
“…The peaks observed at 1384 cm −1 attributes to the presence of flavonoids, indicating good antimicrobial activity. Along with the aforementioned peaks the herbal nanoparticles shows additional peaks such as, 1060 cm −1 corresponds to Research Article SN Applied Sciences (2020) 2:700 | https://doi.org/10.1007/s42452-020-2459-z C-N stretching and vibration respectively [45]. The study shows that the herbal nanoparticles synthesised through wet chemical route shows similar functional groups as that of the herbal nanoparticles synthesised through ball milling in our previous study [18].…”
Section: Characterisation Of Herbal Nanoparticlesmentioning
confidence: 99%